Efeito diferencial do veneno do escorpião Tityus bahiensis em correntes desódio sensíveis e resistentes a tetrodotoxina em neurônios dos Gânglios daRaiz Dorsal de Ratos. - Eder Ricardo de Moraes (2007)
In this study, we tested the effects of Tityus bahiensis scorpion venom on sodium currents recorded from the cell bodies of rat dorsal root ganglion neurons using the whole-cell patch clamp technique. In control conditions, sodium current inactivation at 0 mV exhibited two kinetic components, one fast (tau = 2.15 ± 0.18 ms) and one slow(tau = 13.19 ± 3 ms). In the presence of Tityus bahiensis venom at a dilution of 1:500 (concentration of 5.74 ìg/mL), there was a decrease in the fraction of current comprising the fast component of inactivation (from 80 ± 14 to 60 ± 9 %). The fast time constant of inactivation was not altered significantly (tau = 2.37 ± 0.4 ms), but there was an increase in time constant of slow inactivation (tau = 25.74 ± 3.18 ms). In addition, there was an increase in the fraction of current that inactived slowly (from14.1 ± 0.6 to 36 ± 0.4 %), and the appearance of a persistent component of current that did not inactivate even after long depolarizations (50 100 ms). Additionally, in the presence of Tityus bahiensis venom in experimental conditions there was a very fast component of activation which appeared independently of the presence of a depolarizing pre-pulse (+50 mV). Our results thus agree with those obtained byCampos et al. (2007), and show that a pre-pulse is not necessary for effects on the sodium channel, different from the hypothesis presented by Cestèle et al. (2006). In an attempt of probe which sodium channels isoforms the Tityus bahiensis venom act upon, we used tetrodotoxin (0.25 - 1ìM) in order to isolate pharmacologically tetrodotoxin-resistant sodium currents and submitted these currents to depolarizingpulses to 0 mV and verified the effect of the venom on currents kinetic. Under these experimental conditions, the venom did not produce any effects. Therefore like the venom of the others scorpion, Tityus bahiensis venom contain toxins able to interfere in the kinetics of activation and inactivation of tetrodotoxin-sensitive sodium channels, resulting in alterations typical of á- and â- type toxins.